RE: Is There a More Practical Way for Screening Minimal Hepatic Encephalopathy? - Eyice, Deniz; Ok, Ayşe Merve; Sonsuz, Abdullah; Şenocak, Mustafa Şükrü; Durak, Meliha Nur; Özdemir, Sebati; Canbakan, Billur; Tuncer, Murat; Hatemi, Ibrahim (Turkish Journal of Gastroenterology, 2023)
Cite this article as: Eyice D, Merve Ok A, Sonsuz A, et al. RE: Is there a more practical way for screening minimal hepatic encephalopathy? Turk J Gastroenterol. 2023;34(6):673.